OPTIMALISASI LIMBAH (Eucheuma cottonii) GUNA AKSELERASI PEMANFAATAN ENERGI BARU DAN TERBARUKAN (EBT) DI LINGKUP KEMENTERIAN PERTAHANAN - Anis Sakina Kurniawati; Rudy Laksmono; Ikhwan Syahtaria (Universitas Pendidikan Indonesia (UPI), 2022)
ABSTRACTThe New Renewable Energy Bill or better known as the EBT Bill is a discourse to provide a legal framework regarding policy stipulation, management, supply, and utilization of new and renewable energy. The EBT Bill is expected to be a structured and directed guideline in its implementation from a national to regional scale. With the enactment of the EBT Bill, the use of fossil energy must gradually stop. So it is necessary to look for other alternatives as a source of energy, especially in liquid fuels. One of the potentials that Indonesia as an archipelagic country can exploit is its marine products. Eucheuma cottonii is one of Indonesia's marine products that has the potential to be processed into bioethanol. The Eucheuma cottonii processing industry is spread across various regions of the Republic of Indonesia. Abundant production is also followed by an abundance of residual production waste. This waste is sometimes if not managed properly it will contribute to the emergence of environmental pollution. Therefore, the waste generated from the Eucheuma cottonii processing industry should be optimized by making bioethanol. Eucheuma cottonii waste which is used as bioethanol can be categorized as a 2nd generation biofuel, of course it will not disturb the stability of foodstuffs. This optimization step is carried out as a form of accelerating the use of new and renewable energy. It is also hoped that the utilization of this waste can be used as a source of liquid fuel to support operations within the ministry of defense.Keywords: Bioethanol; Renewable Energy; Eucheuma cottonii ABSTRAKRancangan Undang Undang Energi Baru Terbarukan atau yang lebih dikenal dengan RUU EBT sebagai wacana guna memberi kerangka hukum terkait penetapan kebijakan, pengelolaan, penyediaan, dan pemanfaatan energi baru terbarukan. RUU EBT diharapkan dapat menjadi pedoman yang terstruktur dan terarah dalam implementasinya dari skala nasional hingga daerah. Dengan berlakunya RUU EBT lambat laun penggunaan energi fosil harus dihentikan. Sehingga perlu di cari alternatiif lain sebagai sumber energi terutama pada bahan bakar cair. Salah satu potensi yang kiranya dapat dimanfaatkan Indonesia sebagai negara kepulauan adalah hasil lautnya. Eucheuma cottonii adalah salah satu hasil laut Indonesia yang memiliki potensi untuk diolah menjadi bioetanol. Industri pengolahan Eucheuma cottonii tersebar diberbagai wilayah NKRI. Produksi yang melimpah diikuti pula dengan melimpahnya limbah sisa produksi. Limbah ini lah yang terkadang apabila tidak dikelola dengan baik akan berkontribusi pada munculnya pencemaran lingkungan. Maka sudah seyogyanya limbah yang dihasilkan dari industri pengolahan Eucheuma cottonii dioptimalkan dengan pembuatan bioetanol. Limbah Eucheuma cottonii yang dijadikan bioetanol dapat dikategorikan sebagai biofuel generasi ke-2 tentu saja tidak akan mengganggu kestabilan bahan pangan. Langkah optimalisasi ini dilakukan sebagai bentuk akselerasi pemanfaatan energi baru terbarukan. Adanya pemanfaatan limbah ini pun diharapkan dapat dimanfaatkan sebagai sumber bahan bakar cair untuk mendukung operasional di lingkup kementerian pertahanan.Kata kunci: Bioetanol; Energi Terbarukan; Eucheuma cottonii